Tungsten Trioxide Nanostructures for Photoelectrochemical Water Splitting: Material Engineering and Charge Carrier Dynamic Manipulation - Wang, Yidan; Tian, Wei; Chen, Cheng; Xu, Weiwei; Li, Liang (Advanced functional materials, 2019)
To address the energy crisis and environmental problems, the applications of solar energy have received intensive attention. Converting solar energy to hydrogen using a photoelectrochemical (PEC) cell is one of the most promising approaches to meet future energy demands. As an earth abundant metal oxide, tungsten trioxide (WO3), which has a moderate band gap (2.5–2.7 eV), ideal valence band position, and high resistance to photocorrosion, has been widely utilized in PEC photoanodes. To obtain a WO3 photoanode with high PEC efficiency, tremendous efforts have been made to improve the light absorption capacity, charge carrier dynamics, and oxygen evolution activity. In this report, the recent advances in WO3 photoanode optimization, including morphology design, dopants doping, heterojunction fabrication, and surface modification are summarized. In this review, these developments and representative applications of WO3 photoanodes in unassisted water splitting devices are also discussed. Finally, perspectives on the significant challenges and future prospects for the development of WO3 photoanodes for PEC water splitting are provided. Tungsten trioxide (WO3) is an earth‐abundant semiconductor, which is widely applied as a photoanode for photoelectrochemical (PEC) water splitting. To overcome the inherent shortcomings of WO3 and achieve higher efficiency, various routes have been carried out. The most common approaches and representative works for optimizing WO3 photoanodes are reviewed. The unassisted water splitting devices based on WO3 are also summarized.